Wątki misyjne w nowożytnej ikonograﬁi Świętego Franciszka Ksawerego (w wybranych dziełach sztuki) - Justyna Sprutta, (Annales Missiologici Posnanienses, 2019)
The iconography of Saint Francis Xavier abounds in mission themes. It includes literal and allegorical motives. Symbols are present in this iconography, but the narration prevails. In the mission iconography of Saint Francis Xavier are emphasized: the prophetic dream of a mission in India, teaching, disputing, administering the sacrament of baptism, miracles, the death of Saint Francis Xavier on the island Sancian and his apotheosis which is most often in the “company” of the personiﬁ cation of the continents or mission countries.